Ghana: Agricultural growth key to spur Ghana's economic growth - Resnick, Danielle; Diao, Xinshen; Hazell, Peter B. R.; Kolavalli, Shashidhara (2019)
Ghana has been viewed as one of Africa's political and economic success stories, from maintaining a multi-party democracy, peace and social cohesion to reducing poverty and growing its middle class. Yet, despite 30 years of continuous growth in per capita income and rapid urbanization, the country has not been able to industrialize and most of the workforce is either trapped in traditional agriculture or low-productivity jobs in the services sector. Agriculture holds the potential to help bring about more sustainable and equitable patterns of growth, but public and private actors will need to adjust course in order to achieve it.